1998
DOI: 10.1002/pen.10328
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of blends of poly(ethylene terephthalate) with liquid‐crystalline polymers

Abstract: Poly(ethy1ene terephthalate) (PET) was melt blended with several liquid-crystalline polymers (LCPs), both with and without Ti(OBu), catalyst. The LCPs, referred to as VA, LC5, LC3, and SBH, respectively, were Vectra-A950, Rodrun LC-5000, Rodrun LC-3000, and a laboratory copolyester of sebacic acid (S), 4.4'-diacetoxybiphenyl (B), and 4-acetoxybenzoic acid (H). Their degree of aromaticity decreases in that order. The phase behavior and the morphology of the blends were studied by diEerential scanning calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The formation of the mesophase, as the only ordered phase in the system, provides the enthalpy driving force for reorganization and makes the composition of the two phases become progressively more different as reactions proceed. The segregation of a highly aromatic phase within the aliphaticrich matrix, clearly resulting from compositional differentiation, has also been observed, though more slowly because of the much lower concentration of reactive functional groups, during the reactive blending of PET and preformed LCP, [27] thus confirming the above conclusion.…”
Section: Introductionsupporting
confidence: 74%
“…The formation of the mesophase, as the only ordered phase in the system, provides the enthalpy driving force for reorganization and makes the composition of the two phases become progressively more different as reactions proceed. The segregation of a highly aromatic phase within the aliphaticrich matrix, clearly resulting from compositional differentiation, has also been observed, though more slowly because of the much lower concentration of reactive functional groups, during the reactive blending of PET and preformed LCP, [27] thus confirming the above conclusion.…”
Section: Introductionsupporting
confidence: 74%
“…This is different from blends of PET with Rodrun™, in which the products of transesterification can cocrystallize with PET such that the heat of fusion does not change upon reactive blending. 12 With complete randomization, the PET/ PETBB55 blend becomes random PETBB15, which does not crystallize. Blends of PET and PEN display similar behavior such that the degree of randomness is not a controlling factor to thermal properties of the blend after a certain level of transesterification has been achieved.…”
Section: Thermal Properties Of the Blendmentioning
confidence: 99%
“…However, PET and LCPs are often incompatible and the rates of transesterification in melt blended samples of PET with liquid crystalline polyesters depend on the flexibility of the LCP. 12 The work described herein attempts to reinforce PET with a more compatible blend component. 13 C-NMR spectroscopy has been used to determine the relative amounts of differing monomer dyads in copolyesters 6,13 in cases in which 1 H-NMR spectroscopy is insensitive to copolymer sequence.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, a slight decrease of the fusion temperature T m measured during the second heating run is determined for the p(ET)-p(ETHB) blends, but not for those with VA. On the contrary, no appreciable effect of the presence of any of the LCPs on the enthalpy changes associated with the fusion/crystallization transitions could be observed. In a previous work, [26] some of us investigated the phase behavior of blends of p(ET) with various LCPs, namely VA and other p(ET)-based copolyesters including Rodrunm LC3000 and Rodrunm LC5000 and found that none of the LCPs is miscible with p(ET), although slight interphase interactions could be shown to occur between the p(ET) matrix and all the semi-flexible LCPs. Similar conclusions can be drawn from the DSC investigation of the polymer blends presented in Table 4.…”
Section: Blends Of P(et) With P(ethb) and Glass Fiber Composites Basementioning
confidence: 99%